FLATTENING OF COMPRESSION STEEL DOUBLE-T MEMBERS AFTER UNLOADING BY VARIOUS MEANS (Collection of scientific works «Modern structures of metal and wood», 2019)
Choice  of  arrangement  for  steel  bar  system  reinforcing  is  considered  a multivariate  task.  The  current  development  level  of  methods  for  calculating  and  designing structures,  the  variety  of  possible  arrangements  and  reinforcement  methods  allow  to  develop  a general approach to problems concerning reinforcement optimizing of steel structures. All this envisages calculation and design of structural reinforcement according to a certain arrangement  with  predetermined  parameters  and  under  known  influences.  Only  experimental results are able to confirm validity of the adopted arrangement for strengthening or flattening of structures. The methods for research of steel double-T members bearing resistance after primary loading, unloading, subsequent flattening and secondary loading are described. Samples of various types of residual stress state control were used as experimental ones. After primary compression testing, the experimental samples were flattened by press or by means of idler spindle beading along bulging edges. The results of experimental determination of samples bearing resistance after unloading and flattening are presented. The test results displayed that the bearing resistance of the most samples after flattening was no lower than the samples bearing capacity obtained during initial tests. The research results were used to justify possible further operation of the warehouse building columns. The need for work is caused by the fact that during operation, when moving goods on the floor, damage occurred to individual columns in form of bent flanges or dents in the flanges. For three columns, the curvature exceeded the maximum permissible values. It was found according to the calculation results, that the most loaded column, with a dent in the flange in its lower part, had a significant margin of safety. Guidance  for  ensuring  the  long  and  safe  operating  life  of  columns  is  developed.  For  this purpose,  it  was  proposed  to  flatten  the  flanges  by  means  of  hydraulic  jacks.  Reinforcement  of structures was executed on location.